Improvement of Dispersion and Color Effect of Organic Pigments in Polymeric Films via Microencapsulation by the Miniemulsion Technique - Dongming Qi; Zhijie Chen; Lei Yang; Zhihai Cao; Minghua Wu (Advances in Materials Science and Engineering)
Three primary pigment/poly(n-butyl acrylate-co-styrene) (P(BA+St)) nanocomposites were prepared via encapsulation of the corresponding organic pigments via the miniemulsion technique. The resulting latexes of the P(BA+St)/pigment nanocomposites were filmed in a PTFE mould or printed onto cotton fabric. The morphology of the P(BA+St)/pigment nanocomposites and the dispersion of pigment particles in the latex film and on the printed fabric surface, as well as the adhesion between pigment and adhesive film, were evaluated by transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), 3D digital microscope system (3D-POM), and printing results tests. Attributing to the preprotection of adhesive polymer shell, the self-adhesive P(BA+St)/pigment nanocomposites were homogeneously and firmly dispersed both in the thin latex film and in the adhesive layer on the fiber surface. As a result, the color strength, color fastness, and handle of the fabrics printed by the P(BA+St)/pigment nanocomposites latex were significantly improved, compared to the fabrics printed by the conventional pigment blended latex.